Eutrophication triggers the shift of nutrient absorption pathway of submerged macrophytes: Implications for the phytoremediation of eutrophic waters. (1st June 2019) - Xu, Xiaoguang; Zhou, Yiwen; Han, Ruiming; Song, Kang; Zhou, Xiaohong; Wang, Guoxiang; Wang, Qilin
Abstract: Ecologically restoring eutrophic water bodies by using submerged macrophytes is an economical, effective and sustainable technology worldwide. However, current understanding on the nutrient absorption pathway of submerged macrophytes in freshwater ecosystems, especially under different trophic states, is still limited. In this study, two strategically designed systems were established to form isolated units for preventing nutrient exchange amongst Potamogeton crispus, water column and sediments. Results showed that, in oligotrophic state, P. crispus mainly relied on their roots to absorb nutrients from sediments for maintaining stable growth, with the maximum average height, fresh weight and relative growth rate of 12.85 cm, 4.86 g ind −1 and 0.062, respectively. However, the eutrophic conditions (TN of 4 mg L −1 and TP of 0.3 mg L −1 ) triggered the shift of the nutrient absorption pathway from the roots to the shoots to some extent, that is, the shoots of P. crispus gradually became a remarkable pathway to directly absorb nutrients from the water column. Approximately 49.85% and 18.35% of total nitrogen (TN) and total phosphorus (TP) from overlying water were allocated to the shoots of P. crispus, but had no effects on the growth, photosynthesis and ecological stoichiometric differences ( p  > 0.05). Sediments acting as a nitrogen (N) source supported nearly 11.56% of TN for shoot uptake and simultaneously received around 13.33% of TP subsidy from the overlying water. The no longer sole dependence of submerged macrophytes on their root system to absorb N and phosphorus nutrients indicated that the ability of shoots to absorb nutrients increased with the gradual increase in nutrients in water column. These findings imply that the large specific surface area of shoots is beneficial for restoring eutrophic waters. Graphical abstract: Image 1 Highlights: Nutrient absorption pathway of submerged macrophytes was qualitatively and quantitatively tested. Nutrient enrichment did not affect the growth and eco-physiology of P. crispus. Eutrophic conditions triggered the shift of nutrient absorption pathway from roots to shoots. The absolute acquisition by the roots was the dominant nutrient absorption pathway. The nutrient absorption capacity of shoot is proposed for phytoremediating eutrophic waters.